2007
DOI: 10.1017/s0033291707000840
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental factors affecting self-esteem from age 14 to 17: a longitudinal study of Finnish twins

Abstract: Background-We analysed genetic and environmental influences on self-esteem and its stability across adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 47 publications
1
43
1
Order By: Relevance
“…The results of another study on PIU also showed that the most strongly correlated psychosocial indicators of wellbeing with negative outcomes of the Internet use were loneliness and low self-esteem (Caplan, 2002). In the related literature, there are numerous studies showing that both loneliness (e.g., Boomsma, Willemsen, Dolan, Hawkley, & Cacioppo, 2005;McGuire & Clifford, 2000) and selfesteem (e.g., Kendler, Gradner, & Presscott, 1998;Raevuori et al, 2007) have a genetic component. Moreover, as mentioned earlier, it is argued that comorbidity of two disorders may indicate the casual relationship and/or common etiology shared by them (e.g., Mueser et al, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…The results of another study on PIU also showed that the most strongly correlated psychosocial indicators of wellbeing with negative outcomes of the Internet use were loneliness and low self-esteem (Caplan, 2002). In the related literature, there are numerous studies showing that both loneliness (e.g., Boomsma, Willemsen, Dolan, Hawkley, & Cacioppo, 2005;McGuire & Clifford, 2000) and selfesteem (e.g., Kendler, Gradner, & Presscott, 1998;Raevuori et al, 2007) have a genetic component. Moreover, as mentioned earlier, it is argued that comorbidity of two disorders may indicate the casual relationship and/or common etiology shared by them (e.g., Mueser et al, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…A number of concepts related to self-esteem have been identified: self-confidence, self-depreciation [59], self-concept, self-perception, selfimage, self-worth [60], and (global) academic and social self-esteem [54]. Genetic and environmental determinants of self-esteem have also been investigated [61,62], but no specific determinants of low self-esteem have been identified.…”
Section: Emotional Impairmentmentioning
confidence: 99%
“…A major body of evidence exists for significant genetic effects on self-esteem, with heritability estimates between 30 and 50%, across gender and age (Kamakura et al 2001;Kendler et al 1998;Roy et al 1995). Moreover, broad longitudinal studies indicate that the stability of self-esteem is substantially influenced by genetic factors, as well as by unshared (individual-specific) environmental influences (McGuire et al 1999;Neiss et al 2006;Raevuori et al 2007;Roy et al 1995). The heritability of life satisfaction has been estimated at 38% by Stubbe et al (2005) , in a large sample of Dutch twins and their non-twin siblings.…”
Section: Introductionmentioning
confidence: 99%